„Махiнацiiце я не...“: Klientský systém v České republice a jeho současná transformace - Rumpík, Viktor (Lidé města, 2015)
The aim of the article is to describe the change in the nature of the Ukrainian middleman (client) system from the second half of the first decade of the 21st century to the present. Research took place in Transcarpathia and Pilsen. In these regions, we observe new waves of migration, new legislative restrictions, and new internal, as well as external, strains. All of these factors have an influence on the migrants themselves, and on the Czech labour market. The article responds to the obvious need of re-thinking the structure and the role of the client system. Based on anthropological approaches, such as participant observations and interviews, the article summarises the results of the analysis of the current client system within the institutional theory of migration. The results of the pilot study show the growing extension of the structure of the client system as being a consequence of new migration trends and of the economic recession. We can observe the institutionalisation of aspects and the involvement of formal institutions in the system, as well as restrictions of the use of the Ukrainian middleman (client) system by Ukrainians in the Czech Republic and their displacement by migrants from the European Union, especially from Bulgaria, Romania and Slovakia. The conclusion of the article shows the secondary transformation of the Ukrainian middleman system and its institutionalisation. All issues in this article were analysed using the anthropological micro-optic approach, and they attempt to establish a new discussion of the client system as such.